Implementation of project-based learning models to improve science literacy of junior high school students - Durotun Ayu Fauziah; Erman Erman; Enny Susiyawati; Mohammad Budiyanto (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This study aims to provide an overview of students' scientific literacy effectiveness through project-based learning (PjBL). The type of research used is pre-experimental design research through one group pretest-postest design. The subjects in this study were 22 students of class VII A in junior high school SMP Negeri 3 Sumberejo, Bojonegoro, in the 2022/2023 academic year. The data collection techniques used were tests and questionnaires. Research instruments are science literacy tests and student response questionnaire sheets. The results were analyzed using the N-Gain and t-paired tests with effect size. The implementation observation sheet and the response questionnaire were analyzed descriptively and quantitatively. The results showed that the science literacy ability of grade VII A students of SMP Negeri 3 Sumberejo increased from an average pretest score of 30.6 to 38,03 at the post-test. Students' science literacy ability is in a low category with an average N-Gain of 0.10 with an effect size of 0.63 in the moderate category. Improving students' science literacy skills is also supported by implementing learning that is carried out correctly. The application of project-based learning received a positive response from students. Students find learning using project-based learning environmental pollution material fun, attractive, and easy to understand and use, helping to understand the concept of environmental pollution and practicing science literacy. The implication of this study's results is that students should practice many scientific literacy questions referred to as indicators of scientific literacy competency.